Design of clone‐specific probes from genome sequences for rapid PCR‐typing of outbreak pathogens. (4th April 2014) - López‐Camacho, E.; Rentero, Z.; Ruiz‐Carrascoso, G.; Wesselink, J.‐J.; Pérez‐Vázquez, M.; Lusa‐Bernal, S.; Gómez‐Puertas, P.; Kingsley, R. A.; Gómez‐Sánchez, P.; Campos, J.; Oteo, J.; Mingorance, J.; et al.
Abstract The genome sequence of one OXA‐48‐producing Klebsiella pneumoniae belonging to sequence type (ST) 405, and three belonging to ST11, were used to design and test ST‐specific PCR assays for typing OXA‐48‐producing K. pneumoniae. The approach proved to be useful for in‐house development of rapid PCR typing assays for local outbreak surveillance.